2021
DOI: 10.25029/od.2021.326.21
|View full text |Cite
|
Sign up to set email alerts
|

Estilo de vida, activismo y consumo en influencers medioambientales en Instagram

Abstract: La preocupación por la crisis climática ha generado un activismo medioambiental en las redes sociales liderado en buena parte por influencers. En este artículo se aborda la relación entre dicho activismo, el estilo de vida y las narrativas personales en Instagram a partir de un análisis de caso, la cuenta @vivirsinplastico. Se presenta parte de una investigación en curso de carácter cualitativo, cuyos resultados obtenidos nos permiten sostener, entre otros, que la figura del eco-influencer abre un nuevo modo d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 15 publications
0
8
0
2
Order By: Relevance
“…Third, Chile has a sizeable influencer marketing industry, with influencers who work with local brands and global campaigns, as well as with local and global influencer marketing agencies. These three characteristics make the Chilean case comparable to other countries with active content creation economies and robust infrastructures (Ardèvol and Márquez, 2017; Cornelio et al, 2021; Karhawi, 2020; Tomasena, 2019). They also show how the Chilean case can serve as a basis for broadening our understanding of content creation and influencer industries around the world.…”
Section: Introductionmentioning
confidence: 87%
“…Third, Chile has a sizeable influencer marketing industry, with influencers who work with local brands and global campaigns, as well as with local and global influencer marketing agencies. These three characteristics make the Chilean case comparable to other countries with active content creation economies and robust infrastructures (Ardèvol and Márquez, 2017; Cornelio et al, 2021; Karhawi, 2020; Tomasena, 2019). They also show how the Chilean case can serve as a basis for broadening our understanding of content creation and influencer industries around the world.…”
Section: Introductionmentioning
confidence: 87%
“…The process of compiling images was intended to maximise the differences and variety of contents and approaches, forming what is known as a theoretical sample (Strauss and Corbin, 1994), which we closed when we considered that it had reached its saturation point, as our goal was not to obtain statistically representative data, but a meaningful typology in terms of characterization of the universe studied (San Cornelio et al, 2021). We observed that these types of images were shared in four different types of user accounts in social media, as shown in Table 1:…”
Section: Methodsmentioning
confidence: 99%
“…En el ámbito del activismo medioambiental, las redes sociales y, en general, todo tipo de plataformas web con capacidad para crear comunidad, caso de 9GAG, han jugado un papel decisivo (Roser-Renouf et al, 2014). En general, se ha entendido que el uso de las imágenes resulta especialmente efectivo (O'Neill et al, 2013), muy particularmente a través de los llamados "influencers medioambientales" o "eco-influencers" en redes como Instagram (Haenfler et al, 2012;San Cornelio et al, 2020). A este grupo pertenecen organizaciones como Greenpeace, pero también personalidades destacadas por su activismo climático -Greta Thunberg-.…”
Section: Memes Y Activismo Medioambientalunclassified